HUBUNGAN KECEMASAN DENGAN MOTIVASI KERJA TENAGA KESEHATAN DI PUSKESMAS AMPENAN PADA MASA PANDEMI COVID-19 TAHUN 2020 - Dewi Utary; Ilman Rahaswin Bolkiah; Yolly Dahlia; Dany Karmila (Nusantara Hasana Journal, 2023)
Background: On March 11, 2020 WHO declared COVID-19 a pandemic. Anxiety is an impact of the COVID-19 pandemic experienced by health workers so that it affects work motivation. The study aims to determine the relationship between anxiety and the work motivation of health workers at the Ampenan Health Center during the COVID-19 pandemic. Method :This study is an observational analytic study with a cross sectional design. This study used the HAM-A questionnaire to measure anxiety. Measurement of work motivation was carried out using the MWMS questionnaire. The research sample is 69 respondents. Data analysis using Chi-Square. Result: The results showed that 34.8% of respondents experienced anxiety and 65.2% who were not anxious. Chi-Square analysis obtained a p-value of 0.001 (p-value <0.05), which means that there is a significant relationship between anxiety and the work motivation of health workers at the Ampenan Health Center during the COVID-19 pandemic. Conclusion: There is a relationship between anxiety and the work motivation of health workers at the Ampenan Health Center during the COVID-19 pandemic.